Development of New Hydric Soil Field Indicators: Guidelines for Data Collection and Submission. Issue 1 (7th January 2015) - Berkowitz, Jacob F.; Noble, Chris V.
Abstract : Soil scientists utilize field indicators in the identification of hydric soils as required in a variety of wetland delineation, research, monitoring, and restoration activities. Hydric soil field indicators document the presence of morphologic features associated with hydromorphic soil conditions (e.g., carbon accumulation, Fe/Mn translocation). The National Technical Committee for Hydric Soils retains the responsibility for establishing and approving field indicators of hydric soils in the United States and encourages research supporting the development for new or revised field indicators. Hydric soil indicator studies must establish and instrument paired hydric–nonhydric locations, where data collection requirements include (i) soil descriptions, (ii) evaluation of the Hydric Soil Technical Standard (HSTS), and (iii) analysis of rainfall normality. The following document provides guidance on study design, data collection, and submission requirements for hydric soil field indicator development. Research examining hydric soil field indicators improves the procedures for the identification and management of wetland resources by promoting a greater understanding of hydromorphic soil processes, morphology, and pedology.